KUALITAS NARATIF LAPORAN CORPORATE SOCIAL RESPONSIBILITY: STUDI KORELASI PADA SEKTOR PERBANKAN - Cornelio Purwantini (KRISNA: Kumpulan Riset Akuntansi, 2018)
This study aims to assess the quality of CSR reporting and test the correlation among narrative quality measurements. The Population of the study consists of 29 banks listed on the Stock Exchange (BEI) in 2015. Based on descriptive statistical analysis, the study found that in general the CSR report quality was low, that was shown by the very low value of the mean of optimism ratio, pessimism ratio, numerical ratio, horizon ratio and complexity, and also a readability index that indicate the high level of difficulty of the CSR report to be read. Meanwhile, there are several banks that have presented an excellent report. The results of Spearman correlation test are (1) There is a strong positive correlation between the ratio of optimism and the ratio horizon, (2) There is a fairly strong positive correlation between the ratio of pessimism and numerical ratio, (3) There is a fairly negative strong correlation between the pessimism ratio and numerical ratio, and also between the horizon ratio and the report complexity (residual word), and (5) the other correlations among variables are weak and very weak. Keywords: CSR, narrative reporting quality, and readability